Pengembangan Sistem Informasi Manajemen Masjid Berbasis Android - Liska Della Erlanda; Shinta Esabella (AMIK STIEKOM SUMATERA UTARA, 2023)
The mosque is a place of worship for Muslims, the mosque acts as a center in religious activities of the community and various Muslim communities including formation, education, learning, community empowerment, holiday celebration activities, and others. Nurul Huda Mosque is a large mosque located in Stowe Brang Village, Utan District, Sumbawa Regency, West Nusa Tenggara. Because the system is still a web page, users are still not satisfied with the way it is presented and users often forget and have difficulty in finding web links. This research aims to develop an Android-based Management Information System for Nurul Huda Mosque, Stowe Brang Village, Utan District, by users (worshippers) which aims to produce a more attractive and easily accessible display via android smartphones.Â The results of this study are android-based mosque management information systems on the user side (worshippers) using Extreme Programming (XP) software development methods, Unified Modelling Language (UML) modeling, and flutter darts language and using user experience